Metastatic gastric adenocarcinoma to the cerebrospinal fluid: A report of three cases - Kotwal Sumedha; Bisht Sonali; Dawar Ramesh (Journal of Cytology, 2008)
Neoplastic meningitis is seen in five to ten percent of patients with solid tumors and is characterized by multifocal neurological signs and symptoms. The diagnosis is established by imaging, cerebrospinal fluid (CSF) cytology, and radioisotope CSF flow studies. Gastric adenocarcinoma is a rare cause of neoplastic meningitis. We review here CSF cytology results from our Oncology center obtained over two years and report three cases of gastric adenocarcinoma with cytologically positive CSF.